CHARACTERISTICS OF AGRIPRENEURS IN SOUTHEAST EUROPE: GEM DATA ANALYSIS - Milutinović, Sunčica; Matić, Milenko; Vojinović, Željko; Leković, Bojan; Ivanović-Đukić, Maja (Economics of Agriculture, 2023)
This paper focuses on the factors that decisively influence the practice of agro-entrepreneurship in the early stages of the entrepreneur’s development (demographic, motivational and internationalization factors). The results showed that people who have left their studies are more inclined to start entrepreneurial ventures in the agro-sector than those who are employed full-time or part-time and those who are currently unemployed. It has been proven that older people are more likely to start a venture in this sector. The size of the household proved to be a statistically significant determinant, in the sense that a larger number of household members increases the chances that a person will start a venture. Motives of necessity proved to be key motives for agro-entrepreneurs in the early stages of their development. It has been confirmed that entrepreneurs in the agrosector in the early stages of development do their business predominantly within the borders of the national economy.